Frequency of subclinical mastitis and characterization of the teat of Holstein cows in two municipalities of northern Antioquia, Colombia - Salazar Torres, Lina Maria (2023)
The study aimed to determine the frequency of subclinical mastitis and its association with the shape of the tip and sphincter of the teat in Holstein cows. A descriptive study was carried out in three dairies in the north of Antioquia, Colombia. The tip and sphincter of the teat of 924 mammary quarters (231 animals) were characterized and the presence of subclinical mastitis was determined using the California Mastitis Test (CMT). Results showed that 23% of the quarters and 26.8% of the animals were found with subclinical mastitis. The two most frequent morphologies were the smooth ring sphincter (63%) and the round end nipple (74%), in both cases associated with negative CMT (p<0.0001). Besides, 1.83% of the mammary quarters were not functional.